Washington Street between Milk and Summer Streets, ca. 1941 - Unknown (Tufts Archival Research Center, 2005)
Street-level view northeast of Washington Street between Summer Street to the southwest and Milk Street to the northeast. Filene's Department Store, located at 426 Washington Street at Summer Street, is included in the upper-right corner of the photograph. Signage and awnings adorn the facades of the buildings lining both the northwest and southeast sides of the street. The steeple of the Old South Meeting House, located on the northeast corner of Washington and Milk Streets, is visible in the center of the photograph. Pedestrians fill the street and sidewalks, which are covered in snow. 5 1/2 x 3 3/16, 5 7/8 x 3 1/2 overall Photographs